Photochemistry beyond the red limit in chlorophyll f-containing photosystems - Nuernberg,DJ; Morton,J; Santabarbara,S; Telfer,A; Joliot,P; Antonaru,LA; Ruban,AV; Cardona,T; Krausz,E; Boussac,A; Fantuzzi,A; Rutherford,AW (Science, 2018)
Photosystems I and II convert solar energy into the chemical energy that powers life. Chlorophyll a photochemistry, using red light (680 to 700 nm), is near universal and is considered to define the energy “red limit” of oxygenic photosynthesis. We present biophysical studies on the photosystems from a cyanobacterium grown in far-red light (750 nm). The few long-wavelength chlorophylls present are well resolved from each other and from the majority pigment, chlorophyll a. Charge separation in photosystem I and II uses chlorophyll f at 745 nm and chlorophyll f (or d) at 727 nm, respectively. Each photosystem has a few even longer-wavelength chlorophylls f that collect light and pass excitation energy uphill to the photochemically active pigments. These photosystems function beyond the red limit using far-red pigments in only a few key positions.